2015
DOI: 10.1002/art.39186
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Association Between Hip Osteoarthritis Susceptibility Loci and Radiographic Proximal Femur Shape

Abstract: ObjectiveTo test whether previously reported hip morphology or osteoarthritis (OA) susceptibility loci are associated with proximal femur shape as represented by statistical shape model (SSM) modes and as univariate or multivariate quantitative traits.MethodsWe used pelvic radiographs and genotype data from 929 subjects with unilateral hip OA who had been recruited previously for the Arthritis Research UK Osteoarthritis Genetics Consortium genome‐wide association study. We built 3 SSMs capturing the shape vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 29 publications
(44 reference statements)
1
23
1
Order By: Relevance
“…Table S6). rs4836732, reported to be associated with hip shape by Lindner and colleagues, (6) is in LD (r 2 ¼ 0.49) with rs1885245 ASTN2 SNP we found to be associated with HSM2, both studies observing relationships with femoral head size. Six other SNPs identified across these two SSM studies showed little evidence of association with hip shape in the present study.…”
Section: Astn2supporting
confidence: 64%
“…Table S6). rs4836732, reported to be associated with hip shape by Lindner and colleagues, (6) is in LD (r 2 ¼ 0.49) with rs1885245 ASTN2 SNP we found to be associated with HSM2, both studies observing relationships with femoral head size. Six other SNPs identified across these two SSM studies showed little evidence of association with hip shape in the present study.…”
Section: Astn2supporting
confidence: 64%
“…However, this approach has been successfully applied to better understand disease biology in related complex traits, including joint shape and pain. [46][47][48][49][50] The results of our analyses show that, if further replication is targeted to the specific OA endophenotypes, study power may improve from nearly 0% in the traditional approach to 80% in a sample size of <5000 cases. We used post hoc power calculations, applying the observed variances from the study population of interest to exemplify the difference in the statistical power of the tests we performed.…”
Section: Discussionmentioning
confidence: 79%
“…An intronic SNP within ASTN2 and a 3′‐untranslated region SNP within GLT8D1 were associated with distinct HSMs in 929 subjects with unilateral hip OA in a model built on the superior femur from the unaffected hip. In the same study, a SNP located near IFRD1 was also associated with a combination of 3 distinct modes in a multivariate canonical correlation analysis (CCA) .…”
mentioning
confidence: 89%